Duration of the effects of scarification and raised bed associated with vegetation cover on soybean yield on an Alfisol - Fin, Silvana Spaniol; Marchesan, Enio; Gubiani, Paulo Ivonir; Farenzena, João Alberto Pedroso; Murari, Marcos Stefanello; Coelho, Lucas Lopes; Cargnelutti Filho, Alberto; Aramburu, Bruno Behenck (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to determine the duration of the effects of the mechanical interventions scarification and raised bed on soybean (Glycine max) grain yield on an Alfisol, as well as to evaluate, through physical indicators, if the use of cover plants during winter increases the duration of these effects. The experimental design was a complete randomized block with four replicates. Two factors were evaluated. The first consisted of types of soil preparation systems: SC14, scarification in November 2014; SC15, scarification in November 2015; RB14, raised bed built in November 2014; and RB15, raised bed built in November 2015. The second consisted of the type of cover crop used: winter fallow, oat, ryegrass, and wheat. From November 2015 to April 2016, soybean was cultivated under the different soil preparation systems. Soil density, total porosity, macroporosity, microporosity, soil saturated hydraulic conductivity, soil resistance to mechanical penetration, and soybean grain yield were evaluated. There was no effect of cover plants after one crop season on the maintenance of soil physical attributes. Changes in soil density, total porosity, and resistance to mechanical penetration, promoted by scarification, are noticeable up to at least 18 months. The continuance of these modifications reflects in soybean grain yield in the second harvest.